Archives: Awatara - Culture and Arts Office (Animo Repository, 2021)
Archives: Awatara is an online production by the La Salle Dance Company - Street. It hopes to inspire the viewers with a reinvigorated sense of appreciation for Philippine culture in the pre-colonial period, which has birthed many traditions, tales, and lessons that all deserve to be retold by today’s generation. Be awed with LSDC-Street’s fresh take on Filipino mythology and how they relate these to the present stories of our nation.